Diuretic drug utilization in neonates: a French prescription database analysis - Iacobelli, Silvia; Lorrain, Simon; Rabe, Ezira; Gouyon, Béatrice; Gouyon, Jean-Bernard; Bonsante, Francesco (Frontiers in Pharmacology, 2024)
The use of diuretics is extremely common in infants cared for in neonatal wards, despite the lack of proven efficacy for many conditions. The main objective of this study was to assess the rate of diuretics exposure in a multicenter French cohort. The secondary objectives were to describe the evolution of this exposure over time, the indications, the prescription practices, and the exposure rates among centers.Methods: An observational study was conducted in 40 Level 3 French neonatal intensive care units using the same computerized order-entry system. Neonates hospitalized between January 2017 to December 2021 with a corrected age of between 24 and 44 weeks of gestation at admission were eligible.Results: A total of 86 032 patients were included. The exposure rate was 8.5%, more specifically 29.4% for children born at < 32 weeks of gestation and 3.7% for term-born neonates. There was no significant variation over the study period, but the exposure ranged from 2.4% to 26.5% depending on the center. The main drugs prescribed were furosemide, spironolactone and dopamine with a diuretic purpose. The main indications were "fluid retention", and to a lesser extent "bronchopulmonary dysplasia" and "post-transfusion". For furosemide, the first exposure occurred in mean at 16.5 (±17.8) days of life, mean duration of exposure was 6.2 (±9.5) days, and the cumulative dose was in mean 10.7 (23.9) mg/kg. Conclusions: Diuretic prescription practices vary between centers. The administration of these drugs is often non-evidence based, doses and duration of treatment easily exceed toxic thresholds.